Influences of environmental impact assessment on public acceptance of waste-to-energy incineration projects. (1st July 2021) - Liu, Yong; Xu, Min; Ge, Yujia; Cui, Caiyun; Xia, Bo; Skitmore, Martin
Abstract: Environmental impact assessment (EIA) plays a vital role globally in siting waste-to-energy incineration facilities because of its potentially positive influences on public acceptance of locally unwanted land use (LULU). However, how EIA influences public acceptance of WTE incineration facilities through risk/fairness/trust local residents perceived has not been verified empirically, especially evidences in the Chinese context. In response, this study aims to empirically verify the influence of EIA on public acceptance through perceived risk/fairness and public trust by using a public acceptance model originating from siting nuclear power facilities and data drawn from a questionnaire survey of 401 residents near to four typical waste-to-energy incinerators in the Yangtze River Delta region, China. Structural Equation Modeling (SEM) analysis shows that EIA tends to increase public trust and perceived fairness, and decrease perceived risk; public trust and perceived fairness tend to decrease perceived risk; while public acceptance of WTE incinerator projects is enhanced by increased public trust and decreased perceived risk. The findings contribute to the knowledge body of environment management and siting potentially hazardous facilities by exploring the specific impact of EIA on public acceptance, and are of great significance for local governments and other authorities in decision-making and locally unwanted land use. Highlights: Influences of EIA on public acceptance of WTE incineration projects is investigated. Public acceptance towards WTE incinerators in China is still at a very low level. Public acceptance can be enhanced by EIA through perceived fairness/risks and trust. Public acceptance is affected by such demographic variables as age, education level, etc.